Expression and Function of Tetraspanins and Their Interacting Partners in B Cells - Zou, Fagui; Wang, Xu; Han, Xinxin; Rothschild, Gerson; Zheng, Song Guo; Basu, Uttiya; Sun, Jianbo (Frontiers in Immunology, 2018)
Tetraspanins are transmembrane proteins that modulate multiple diverse biological processes including signal transduction, cell-cell communication, immunoregulation, tumorigenesis, cell adhesion, migration, and growth and differentiation. Here we provide a systematic review of the involvement of tetraspanins and their partners in the regulation and function of B cells including mechanisms associated with antigen presentation, antibody production, cytokine secretion, co-stimulator expression, and the immunosuppression. Finally, we direct our focus to the signaling mechanisms, evolutionary conservation aspects, expression, and potential therapeutic strategies that could be based on tetraspanins and their interacting partners.